Antibacterial Activity and Potential Of Natural Textile Dyes From Sea Water Bacteria - Andang Syaifudin; Sutrisno Sutrisno (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2022)
This research aims to determine the potential of bacterial isolates from Marina beach seawater to be used as natural textile dyes and to test their antibacterial ability. The media used for culturing bacteria is a zobel synthesis medium with a mixture of seawater. The results of the isolation and extraction of color pigments obtained a red color with a characteristic wavelength of 535 nm and has a variety of chemical content results. Pigment immersion trials using 3 types of fabric, namely cotton, primisima and dobby fabric. The results of immersion with ethanolic solvent obtained optimum results for 12 hours and with the addition of mordant (Fe.H2O4S.7H2O), the color of the fabric is strong enough to withstand washing with detergent and sunlight. From the results of the study, data showed that the dyed primisima fabric gave a reduction or inhibition of the growth of E. coli bacteria by 9% while the inhibition of S. aureus bacteria was 116%. The pigment has the potential to be used as a dye for batik cloth with the provisions of optimizing to find the right reinforcement or mordant. This study has implications for the discovery of red pigment-producing bacteria from the isolation of seawater at Marina Semarang beach.